Abundance and Characteristics of Microplastics in Coral Reefs at Penimbangan Waters - Muhmad Abraham; Yulianto Suteja; I Gusti Ngurah Putra Dirgayusa (Advances in Tropical Biodiversity and Environmental Sciences, 2025)
Coral reefs are a vital component of marine ecosystems, playing a crucial role in providing and protecting marine biodiversity. However, recent studies have found the presence of microplastics in corals, which have been proven to threaten their health. This study aims to identify the abundance and characteristics of microplastics in coral reefs in the waters of Penimbangan Beach. A total of 12 coral samples were collected from two stations selected based on the presence of coral reefs in the area and then analyzed in the laboratory. Microplastic separation was carried out using hydrochloric acid (HCl) and sodium chloride (NaCl) solutions. Subsequently, an analysis was conducted to determine the abundance and identify the shape, size, and color of the microplastics. The research results showed that the highest microplastic abundance was found at Station 1 (3.5 particles/gram), while the lowest was at Station 2 (1.6 particles/gram). The characteristics of microplastics found were predominantly fibers (94.6%), followed by fragments and granules. The most commonly found microplastic size was 0.001–1 mm (53%), followed by 1–5 mm. The dominant microplastic color was black, followed by blue, red, transparent, and brown.